The Origin of Religious Tolerance and the Application of Pancasila - Brehm, Wolfgang (Graduate School of UIN Syarif Hidayatullah Jakarta, 2022)
The main purpose of this article is to denote the historical fact that Piagam Jakarta does not only instruct the state to apply the Sharia for the Muslim population but it also softens the binding force of the Sharia by obligating the state to harmonize the requirements of Sharia with the comprehensive understanding of Pancasila in its entirety. The research finding: the historical fact indicates that the consent of the representatives of the Muslim group in Panitia Persiapan Kemerdekaan Indonesia (PPKI) as well as in Badan Penyelidik Usaha Persiapan Kemerdekaan Indonesia (BPUPKI) is to the abandonment of the Islamic Clause (klausula tentang Islam). They called for the deletion of any reference to Islam. Hence, for this research, it can be concluded that the Islamic Clause does not present a counter-draft but forms a preliminary stage of Pancasila and its first sila. This conclusion is also strengthened by linguistic rules referring to the word “Ketuhanan” abstaining from making any statement about the attitude of people towards God. Therefore, replacement of the Islamic Clause with the term “Ketuhanan Yang Maha Esa” has removed any boundary which would have been established by any religious doctrines against the inclusion of citizens with equal rights and has opened the way for Indonesia to implement the universal human rights to their full extend. The research is done through socio-legal approach. It sees historical data from socio-legal perspectives.